Combination of Gymnastics and Warm Compresses for Reducing Menstrual Pain (Dysminore) in Young Girls at SMA 1 West Pasaman - Endang Sari; Elwitri Silvia; Welly Handayani (Institute of Computer Science (IOCS), 2022)
Menstrual pain or dysmenorrhea is a problem the most common reasons for a decrease in women's activity during menstruation, for example not going to school. According to data from the World Health Organization (WHO) 85% of women experience dysmenorrhea with 15-20% experiencing severe dysmenorrhea. Handling this problem in a non-pharmacological way needs to be developed, for example by exercising and warm compresses. The purpose of this study was to determine the effect of a combination of exercise and warm compresses on reducing dysmenorrhea in young women at SMA 1 Pasaman Barat. The type of research used was a pre-experimental design with one group pre and post test. Samples were obtained based on inclusion criteria as many as 30 people. data acquisition through observation sheets in the form of a Numerical Rating Scale (NRS). Of the 30 respondents before being given treatment as much as 20 (67%) experienced moderate pain during menstruation and 6 respondents (20%) experienced mild pain during menstruation and after being given treatment as many as 18 respondents (60%) became painless and 6 respondents (20% ) to mild pain. From the analysis of the data obtained value (p value = 0.0001). This p value indicates a relationship between a combination of exercise and warm compresses on reducing pain. Based on the results of this study it can be concluded that doing a combination of exercise and warm compresses has an effect on reducing menstrual pain in young women at SMA 1 Pasaman Barat.